MRI to investigate iliac artery wall thickness in triathletes - Regus, S.; Almási-Sperling, V.; Janka, R.; Rother, U.; Lell, M.; Meyer, A.; Lang, W. (The Physician and Sportsmedicine, 2018)
Objectives: Endofibrosis was first described in endurance athletes. This rare disease is characterized by intimal hyperplasia of iliac arteries. Due to non-specific symptoms diagnosing could be very challenging and delayed. This represents a serious problem not only for affected athletes but also for consulting physicians. The aim of this study was to analyze intimal thickness of iliac arteries using non-contrast magnetic resonance imaging (MRI) in competitive triathletes suffering from exercise induced leg pain consistent with symptoms caused by endofibrosis.